2014
DOI: 10.5604/20831862.1124568
|View full text |Cite
|
Sign up to set email alerts
|

<strong>GENOME-WIDE ASSOCIATION STUDY IDENTIFIES THREE NOVEL GENETIC MARKERS ASSOCIATED WITH ELITE ENDURANCE PERFORMANCE </strong>

Abstract: To investigate the association between multiple single-nucleotide polymorphisms (SNPs), aerobic performance and elite endurance athlete status in Russians. By using GWAS approach, we examined the association between 1,140,419 SNPs and relative maximal oxygen consumption rate (V.O2max) in 80 international-level Russian endurance athletes (46 males and 34 females). To validate obtained results, we further performed case-control studies by comparing the frequencies of the most significant SNPs (with P < 10−5-10−8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 33 publications
0
59
2
Order By: Relevance
“…Additionally, the frequency of the C allele was significantly higher in elite endurance athletes in comparison with nonelite endurance athletes, Russian and European controls, and power athletes [5]. Consistent with the hypothesis, the authors also reported that the C allele was associated with activation of erythropoiesis (high level of hemoglobin, high number of reticulocytes and erythrocytes), while the A allele with activated granulopoiesis (high number of neutrophils and greater leukocyte/erythrocyte ratio).…”
Section: Nfia-as2 Rs157231 с Allelementioning
confidence: 72%
See 4 more Smart Citations
“…Additionally, the frequency of the C allele was significantly higher in elite endurance athletes in comparison with nonelite endurance athletes, Russian and European controls, and power athletes [5]. Consistent with the hypothesis, the authors also reported that the C allele was associated with activation of erythropoiesis (high level of hemoglobin, high number of reticulocytes and erythrocytes), while the A allele with activated granulopoiesis (high number of neutrophils and greater leukocyte/erythrocyte ratio).…”
Section: Nfia-as2 Rs157231 с Allelementioning
confidence: 72%
“…By performing GWAS of 80 Russian endurance athletes, Ahmetov et al [5] have shown that the rs157231 CC genotype of the NFIA-AS2 gene was associated with high VO 2max in three subgroups of athletes (male and female middle and short endurance athletes; female long endurance athletes). Additionally, the frequency of the C allele was significantly higher in elite endurance athletes in comparison with nonelite endurance athletes, Russian and European controls, and power athletes [5].…”
Section: Nfia-as2 Rs157231 с Allelementioning
confidence: 98%
See 3 more Smart Citations